Influence of motor complete spinal cord injury on visceral and subcutaneous adipose tissue measured by multi-axial magnetic resonance imaging - Gorgey, Ashraf S. (Maney Publishing, 2011)
OBJECTIVE: Abdominal obesity conveys substantial health risks, in association with high levels of visceral adipose tissue (VAT), subcutaneous adipose tissue (SAT) and an increased proportion of VAT to SAT. The purposes were to determine the influence of spinal cord injury (SCI) on the associations between single axial cross-sectional area (CSA) slices and the average CSA or volumes of VAT and SAT across multi-axial slices of magnetic resonance imaging (MRI); and the relationships relative to the whole body composition and anthropometrics. METHODS: Thirteen healthy male participants with traumatic motor complete SCI underwent fast spin-echo MRI to measure VAT and SAT across multi-axial slices, followed by dual-energy X-ray absorptiometry to measure whole body fat-free mass (FFM) and fat mass (FM). Waist circumference (WC) was also measured in the seated position. RESULTS: The trunk CSAs of VAT and SAT were 99 ± 51 and 164 ± 69 cm(2), respectively, and the ratio of VAT to SAT was 0.68 ± 0.33. The CSAs of VAT and SAT at a single slice strongly predicted the average CSA and modestly predicted the volumes across multi-axial slices. VAT and SAT represented 5.7 ± 1.8% and 9.7 ± 3.2% of the total body FM, respectively. Percent body FFM was negatively related to VAT and SAT volumes, but not to a single axial CSA. CONCLUSION: A single slice CSA can modestly predict the volume of multi-axial slices in individuals with SCI, yet it is not related to any of the body composition variables. Increased percent FFM is associated with a reduction in VAT and SAT volumes measured across multi-axial slices. The ratio of VAT to SAT is greater than 0.4, suggesting that individuals with SCI are at high risk of developing metabolic sequelae.